Implementasi Etnomatematika Berbasis Budaya Lokal dalam Pembelajaran Matematika pada Jenjang Sekolah Dasar - Rizki Wahyu Yunian Putra; Popi Indriani (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2017)
This study aims to describe the Lampung handicraft "tapis and siger" into learning mathematics at Elementary School level. The data obtained in the form of qualitative data while the source obtained from observations, documentation and informants associated with Lampung handicraft the "tapis and siger". The instrument in this study is the researcher itself. The tools used are interview guides, documentation guides, and observation guidelines. Data validity technique by data triangulation through data source checking, analizing descriptive qualitative. The results showed that the motif of woven cloth fabric Sanggar Rahayu consists of geometric motifs, humans, animals, and motifs of plants, while Siger Lampung has a mathematical element in which the triangle. Cultural-based math learning is needed in schools especially in elementary school, because not only to understand the concept of mathematics but learners are also introduced and love culture early on.